2001
DOI: 10.1037/h0089539
|View full text |Cite
|
Sign up to set email alerts
|

The Establishing Focus protocol: Training for collaborative agenda setting and time management in the medical interview.

Abstract: providers were more satisfied, perceived more complete problem elicitation and collaborative prioritization.These promising pilot data indicate a need to do an expanded study of the EF protocol. Ideas for research and training are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 43 publications
1
34
0
1
Order By: Relevance
“…The findings question the assumption that time pressure or physician anxiety about case difficulty account for lowered rates of solicitation. 15,21 This study is limited by the fact that our principal outcome measure, the Index of Understanding, employs a relatively new instrument without a known sensitivity. It may have been unable to discriminate differences in the understanding levels of physicians who interrupted their patients and those who did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings question the assumption that time pressure or physician anxiety about case difficulty account for lowered rates of solicitation. 15,21 This study is limited by the fact that our principal outcome measure, the Index of Understanding, employs a relatively new instrument without a known sensitivity. It may have been unable to discriminate differences in the understanding levels of physicians who interrupted their patients and those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Yet the templates developed for taking a survey of patient concerns sometimes recommend physician activity that would constitute interruption by the Beckman-Frankel definition. 14,15 Further, Beckman and Frankel themselves acknowledge that physician interruption might sometimes help patients formulate their concerns (p. 695). 5 Marvel et al found…”
mentioning
confidence: 99%
“…Prior observational studies of actual care have demonstrated that agenda pursuit can take a variety of forms [8,16,21,37]. We focused on 'essential elements' [16] involving physicians' questioning strategies for eliciting additional concerns that occurred after patients' presentations of their initial or chief concern.…”
Section: Incidence Of Questionsmentioning
confidence: 99%
“…As a component of patient-centered communication [15,[23][24][25], and ultimately of shared decision making [26], agenda pursuit is now a staple of textbooks on medical interviewing [27][28][29] and is a frequent component of physiciantraining programs [5,18,22,[30][31][32][33][34][35]. It has also been integral to innovations in medical interviewing, such as the 'four-habits model' [26,36] and the 'establishing-focus protocol' [16,21,37]. In addition to reducing the incidence of unmet concerns [2], up-front agenda pursuit is associated with patient satisfaction [14], improved physician understanding of patients' concerns [12], and a decreased incidence of late-emerging concerns [8,38].…”
Section: Introductionmentioning
confidence: 99%
“…In patient interviews, novice clinicians often dive prematurely 6 into symptoms and possible diagnoses. A patient-centered approach is more effective and ultimately more efficient, starting with open-ended questions to explore the patient's agenda and view of the illness experience.…”
Section: P3 Mentoring Processmentioning
confidence: 99%